Measuring the Honey Bee Research Output: Scientometrics Analysis from 2004 To 2019 - Sivankalai, S., Sivasekaran, K., Virumandi , A., Sharmila 4 (International Journal of Modern Agriculture, 2021)
This effort purposes to arrange for a complete study of the accessible investigation of statistics in honey bees through literature analysis. The research advancements within this research field from 2004 to 2019 are addressed using the Web of Science database. The results from the 10136 articles analyzed and indicate that in the research field is the focus of research nowadays by the USA 3114 produced more articles, followed by Germany, Brazil, UK, and Peoples R China. We dignified an output mark for respective authors and the maximum creative authors in the honey bee field Oldroyd BP (112), Evans JD (109), and Robinson GE (102). It is clear that the US Department of Agriculture institutes Research Service form is the biggest procedure of the total citations (16902) followed by The University of Sao Paulo (14573), Arizona state university (11662) followed by University Illinois (10947) has contributed. To the best of our knowledge, our study was the first in this area and we have been brought more support to further research.